Three‐dimensional endovaginal ultrasound assessment using the levator ani deficiency score in primiparas: A replication study - Emilia Rotstein; Vilhelmina Ullemar; Marianne Starck; Gunilla Tegerstedt (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction It is essential to assess the levator ani properly as part of clinical care in patients presenting with pelvic floor dysfunction. The levator ani deficiency scoring system is a previously published method to assess levator ani defects with three‐dimensional endovaginal ultrasound. The primary aim of this study was to determine the intra‐ and interrater reliability of the levator ani deficiency score in a cohort of non‐instrumentally delivered primiparas. Material and methods Primiparas (n = 141) were examined at least 1 year after vaginal birth. Three‐dimensional endovaginal ultrasound volumes were acquired by a single examiner using two different automated ultrasound probes. The volumes were analyzed by two separate raters who were blinded to each other's assessments. Descriptive statistics were calculated for levator ani deficiency score and categorized into three levels (mild, moderate, severe). Kendall's tau‐b was calculated for intra‐ and interrater comparisons. Results Intrarater comparisons of levator ani deficiency score and levator ani deficiency category were high (Kendall's tau‐b ≥0.80 for Rater 1; >0.79 for Rater 2). Interrater comparisons of levator ani deficiency score and levator ani deficiency category were also high (Kendall's tau‐b >0.9 for assessment 1 and >0.78 for assessment 2). Varying by rater, probe and assessment, 75.9%–80.1% of the study population had no/mild deficiency, 6.4%–9.2% had moderate deficiency, and 4.3%–6.4% had severe levator ani deficiency. Conclusions The levator ani deficiency scoring system is a feasible method to assess defects of the levator ani muscle and can be reproduced with high intra‐ and interrater correlations. Using the scoring system in clinical practice may facilitate concordant assessment between different examiners. However, the system should be used to support clinical findings and symptomatology and not as a screening tool, as the score is lacking the category of no levator ani deficiency.